2016
DOI: 10.1136/tobaccocontrol-2016-053061
|View full text |Cite
|
Sign up to set email alerts
|

What is included with your online e-cigarette order? An analysis of e-cigarette shipping, product and packaging features

Abstract: Background The electronic cigarette industry is growing, with youth using e-cigarettes at higher rates than they are using cigarettes, and retail and online sales projected to reach $10 billion in 2017. Minimal regulation of the production and marketing of e-cigarettes exists to date, which has allowed companies to promote unsupported claims. We assessed the shipping, product features and packaging of a wide variety of e-cigarettes purchased online by adults and youth. Methods The most popular internet e-cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In light of the place‐of‐purchase results of this study, there may be challenges in ensuring e‐cigarettes meet quality standards and are not marketed as an evidence‐based method of quitting smoking. A recent study of 125 online orders of e‐cigarettes found many did not have instructions for use, product information or health warnings, and some had unsupported claims and/or were leaking e‐liquid or battery fluids 32 . Discussions about how to regulate e‐cigarettes should therefore consider regulating the online sale, advertising and promotion of e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the place‐of‐purchase results of this study, there may be challenges in ensuring e‐cigarettes meet quality standards and are not marketed as an evidence‐based method of quitting smoking. A recent study of 125 online orders of e‐cigarettes found many did not have instructions for use, product information or health warnings, and some had unsupported claims and/or were leaking e‐liquid or battery fluids 32 . Discussions about how to regulate e‐cigarettes should therefore consider regulating the online sale, advertising and promotion of e‐cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, manufacturing could also be improved in terms of the design (e.g., limitation of the power output) and quality of EC devices. Poor workmanship in terms of the quality of the batteries and heating elements can increase the concentration of toxic metals found in aerosolant (Kong et al 2016;Loewenstein and Middlekauff 2017). Overall, ECs deliver a wide array of aerosolants, ranging from some known irritants to carcinogens.…”
Section: How Manufacturing Can Affect the Composition Of Ec Liquids Amentioning
confidence: 99%
“…Many e-liquid manufacturers do not report health warnings, chemical sources, manufacturing process, exhaustive ingredient lists, or concentrations (Kong et al 2016). ECs are capable of delivering nicotine in their vapour, with the amount of nicotine varying based on the solution, power of the device, or smoking topography (e.g., puff duration) (Trtchounian et al 2010;Spindle et al 2015;Talih et al 2015).…”
Section: How Manufacturing Can Affect the Composition Of Ec Liquids Amentioning
confidence: 99%
“…9 One US study identified worrying deficiencies in the online supply of e-liquids, including inadequate systems for verifying the age of buyers, the lack of instructions about how to use or store the products, and delivered products that were leaky. 10 ENDS e-liquids contribute to both unintentional and intentional (suicidal) nicotine poisonings, 11 as discussed by Wylie and colleagues in this issue. 12 Those most at risk of unintentional poisoning are children under 5 years of age, particularly following ingestion of fluids from e-liquid bottles.…”
mentioning
confidence: 99%
“…The Australian vapour product retail market in 2017 was estimated be worth $AU50.1 million, also primarily open systems ($AU46.8 million); 79% of retail purchases were made online . One US study identified worrying deficiencies in the online supply of e‐liquids, including inadequate systems for verifying the age of buyers, the lack of instructions about how to use or store the products, and delivered products that were leaky …”
mentioning
confidence: 99%